Genome-Wide Association Analysis Identifies Loci for Powdery Mildew Resistance in Wheat - Chen, Xiangdong; Wang, Haobo; Fang, Kaiqiang; Ding, Guohui; Dong, Nannan; Dong, Na; Zhang, Man; Zang, Yihao; Ru, Zhengang (Agronomy (Basel), 2025)
Wheat (Triticum aestivum L.), a staple crop of global significance, faces constant biotic stress threats, with powdery mildew caused by Blumeria graminis f. sp. tritici (Bgt) being particularly damaging. In this study, a multi-year single-site experiment was conducted to minimize the environmental impacts, and a five-level classification system was used to assess powdery mildew resistance. A 660K SNP array genotyped 204 wheat germplasms, followed by GWAS. SNP loci with a −log10(p) > 3.0 were screened and validated across repeats to identify those associated with powdery mildew (Pm) resistance. Twelve SNPs were consistently associated with Pm resistance across multiple years. Of these, three colocalized with previously reported Pm-resistance gene or QTL regions, and the remaining nine represented potentially novel loci. The candidate genes identified included leucine-rich repeat (LRR) and NB-ARC immune receptors, as well as pathogen-related, thioredoxin, and serine threonine-protein kinase genes. Overall, the SNP loci and candidate genes identified in this study provide a basis for further fine mapping and cloning of the genes involved in relation to Pm resistance.